Role of Tourism in Poverty Alleviation A Case Study of Kerala - Nargeskhatoon Bozorgaghideh and Resia Beegam.S
This paper gives an overview of tourism and poverty reduction and highlights major policy statements in ‘pro-poor tourism’. After providing a brief outline of the historical survey of tourism, it discusses various aspects that play a crucial role in tourism development with a focus on poverty reduction, economic performance, livelihoods, land and natural resources, food security, environmental sustainability, climate change, etc. The key message of this paper is initiatives on pro-poor tourism taking in to account realities on the life of local people. It also shows the vital role of tourism in effectively tackling the root causes of poverty, inequality and problems of environmental degradation and climate change in the context of globalization. It also scans the effectiveness of Kerala’s tourism in the growth of the economy of Kerala in particular and its contribution to stringing Indian economy. Different types of tourism are influential in the alleviation of poverty.